BS EN 4496. Aerospace series. Screw, 100° countersunk normal head, offset cruciform recess, close tolerance normal shank, short thread, in titanium alloy, anodized, with aluminium pigmented coating. Classification: 1 100 MPa (at ambient temperature)/315 °C. (2nd July 2020) - British Standards Institution,
No abstract available